Peran Kepala Sekolah dalam Peningkatan Mutu Guru di SMK Muhammadiyah 1 Blora Tahun 2015 - Utami, Yeri (JURNAL PEDAGOGY, 2017)
The background of this research is not an increase in the quality of teachers at SMK Muhammadiyah 1 Blora significantly, thus the need for the principal's role as leader of the institution to continue strive for improving the quality of teachers. Because teachers are the main components that play an important role in improving the quality of education. The aim of this study is to describe the principal's role in improving the quality of teachers, the implementation of the improvement of teacher quality, improvement strategies of teacher quality, constraints inimproving the quality of teachersinSMK Muhammadiyah I Blora. This study is a qualitative research with phenomenological approach and naturalistic. This research was conducted in SMK Muhammadiyah I Blora. Data was collected by 1) observation, 2) interviews, 3) documentation. Technique authenticity of data is done with the credibility test, tranferabilitas testing, reliability testing, and test komfirmabilitas. The analysis of data was done by data reduction, data presentation, and verification concluded. Results of the study were 1) The principal role as educator, manager, administrator, supervisor, leader, innovator and motivator in improving teacher quality, 2) Implementation of Quality Improvement of Teacher consists of three phases, including planning, implementation / execution, and evaluation, 3) the strategy which is usedthe principals in improving the quality of teachers is to enhance the dignity of teachers in social, cultural and economic conducted with due regard to the welfare of teachers, the other strategies is to includin teachers in the program of improving the professionalism of teachers programmed by the government, 4) constraints to improve the quality of teachers facing the principal were: a) constraints increase teacher qualifications include cost issues and lack of free time teachers, as well as a considerable distance to continue his studies,b) constraints to increase the competence of teachers such problems considerable distance for training teachers, the teaching hours are not effective when there are teachers who can not teach because the program improving the professionalism of teachers, there are still teachers who are less aware of the importance of improving the quality of teachers c) constraints increase teacher performance including a lack of mastery of teachers towards technology, and facilities are inadequate.